Quality of reduced-fat meat emulsion: effect of pre-emulsified duck skin and hydrocolloids - Yong, Hae In (J Food Sci Technol, 2020)
This study explored the impact of reduced-fat meat emulsion with pre-emulsified duck skin and hydrocolloids on physicochemical properties such as cooking loss, emulsion stability, apparent viscosity, protein solubility, and texture profile analysis. Six different reduced-fat meat emulsions were produced: control (pork back fat), T1 (duck skin, DS), T2 (pre-emulsified with duck skin, PDS), T3 (PDS + 2% carrageenan), T4 (PDS + 2% alginate), T5 (PDS + 2% pectin), and T6 (PDS + 2% guar gum). Moisture content, protein content, yellowness, and apparent viscosity of reduced-fat emulsion with PDS and hydrocolloids were all higher (P < 0.05) than control. Cooking loss and emulsion stability of T4 and T6 were lower (P < 0.05) than the control values. Cooking loss and total fluid separation were greatest (P < 0.05) for T5. Fat content of reduced-fat emulsion with PDS was lower (P < 0.05) than that of the control. Meat emulsion comprising PDS with alginate resulted in superior physicochemical properties compared to the other reduced-fat meat emulsion.